Lung transplantation for interstitial lung disease in idiopathic inflammatory myositis: A cohort study. Issue 12 (3rd September 2022) - Rivière, Amélie; Picard, Clément; Berastegui, Cristina; Mora, Victor Manuel; Bunel, Vincent; Godinas, Laurent; Salvaterra, Elena; Rossetti, Valeria; Savale, Laurent; Israel‐Biet, Dominique; Demant, Xavier; Bermudez, Julien; et al.
Abstract : In patients with interstitial lung disease (ILD) complicating classical or amyopathic idiopathic inflammatory myopathy (IIM), lung transplantation outcomes might be affected by the disease and treatments. Here, our objective was to assess survival and prognostic factors in lung transplant recipients with IIM‐ILD. We retrospectively reviewed data for 64 patients who underwent lung transplantation between 2009 and 2021 at 19 European centers. Patient survival was the primary outcome. At transplantation, the median age was 53 [46–59] years, 35 (55%) patients were male, 31 (48%) had classical IIM, 25 (39%) had rapidly progressive ILD, and 21 (33%) were in a high‐priority transplant allocation program. Survival rates after 1, 3, and 5 years were 78%, 73%, and 70%, respectively. During follow‐up (median, 33 [7–63] months), 23% of patients developed chronic lung allograft dysfunction. Compared to amyopathic IIM, classical IIM was characterized by longer disease duration, higher‐intensity immunosuppression before transplantation, and significantly worse posttransplantation survival. Five (8%) patients had a clinical IIM relapse, with mild manifestations. No patient experienced ILD recurrence in the allograft. Posttransplantation survival in IIM‐ILD was similar to that in international all‐cause‐transplantation registries. The main factor associated with worse survival was a history of muscle involvement (classical IIM). In lung transplant recipients with idiopathic inflammatory myopathy, survival was similar to that in all‐cause transplantation and was worse in patients with muscle involvement compared to those with the amyopathic disease. Abstract : A retrospective multicenter study shows that patient survival after lung transplantation for myositis‐related interstitial lung disease is comparable to that reported in international registries for all causes combined.